(untitled) (Konferensiyalar | Conferences, 2023)
The article is about the communication between the Information Service and the audience. The history of the creation of the telegram channel, which is considered one of the official gifts of the Nukus branch of the Samarkand University of veterinary medicine, animal husbandry and biotechnology on the internet, and the content of previously posted articles on it were analyzed.